Kadmij in svinec v živilih rastlinskega izvora, pridelanih na območju Teharij in Medloga (MO Celje) - kazalca onesnaženosti okolja - Eržen, Ivan (Zdravstveno varstvo, 2005)
Introduction. Industrial development in the last century brought about industrial pollution of soil in the Celje region, as indicated by the testing of environmental soil for toxic metals. The objective of this study was to determine the relationship between cadmium and lead contents in foods of plantorigin produced in the Celje region and pollution of soil by these toxic metals in one part of the region. Method of work. In 2002, 168 samples of foods made from crops cultivated at the Teharje (113) and Medlog (55) farms were tested for cadmium and lead contents. The results were evaluated in accordance with current environmental legislation and compared with the testing of foods of plant origin produced in other Slovene regions. Results. The foods tested had a high cadmium content, which frequently exceeded maximum permitted levels. In the majority of foods tested the levels of cadmium were notably higher than in foods produced elsewhere in Slovenia. The levels of cadmium were highest in wheat, lettuce, beat, carrot and potato samples, and exceeded notably the mean cadmium levels for Slovenia. Foods madefrom plants cultivated in the Teharje region had higher cadmium levels than those from the Medlog area. The lead content in the crops was similar to lead levels in foods made from plants cultivated in other Slovene regions. Conclusion. In view of the above mentioned findings, increased cadmium levels in the soil of Teharje and Medlog remain a major environmental issue, the moreso because farms in these regions yield relatively good crops and a considerable amount of domestic produce is sold on the market. Also, most homegrown crops are the only source of nutrition for the local population. Theresults of the study show that cadmium content in foods can be used as an indicator of cadmium load in soil. The same conclusion , however, cannot be drawn for lead.
Keywords: Celje; kadmij; svinec; težke kovine; živila